2016
DOI: 10.1016/j.aucc.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

What is the relationship between elements of ICU treatment and memories after discharge in adult ICU survivors?

Abstract: The body of literature on the relationship between elements of ICU treatment and memories after ICU discharge is small and at its early stages. Larger studies using rigorous study design are needed in order to evaluate the effects of different elements of ICU treatment on the development of memories of the ICU during recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 38 publications
1
40
3
1
Order By: Relevance
“…The content of the delusional memories in our study did not seem to differ from earlier studies, being strange, scary and lifethreatening, but yet closely related to real life events (Svenningsen, Egerod, & Dreyer, 2016;Wade et al, 2015). Aitken et al (2016) concluded that deep sedation in ICU patients often led to amnesia and delusional memories, whereas lightly sedated patients had more stressful experiences.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The content of the delusional memories in our study did not seem to differ from earlier studies, being strange, scary and lifethreatening, but yet closely related to real life events (Svenningsen, Egerod, & Dreyer, 2016;Wade et al, 2015). Aitken et al (2016) concluded that deep sedation in ICU patients often led to amnesia and delusional memories, whereas lightly sedated patients had more stressful experiences.…”
Section: Discussioncontrasting
confidence: 63%
“…Aitken et al. () concluded that deep sedation in ICU patients often led to amnesia and delusional memories, whereas lightly sedated patients had more stressful experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aber auch beängstigende wahnhafte, halluzinatorische Pseudoerinnerungen an den Aufenthalt auf der Intensivstation finden sich je nach Studie und Operationalisierung bei rund einem Viertel der Patienten [28,29]. Diese Pseudoerinnerungen werden im intensivmedizinischen Umfeld u. a. durch eine tiefe Sedierung, Kortikosteroide und Glukoseinfusion zur Behandlung einer Hypoglykämie hervorgerufen [30]. Sie stellen einen Risikofaktor für die spätere Entwicklung von Symptomen einer PTBS, aber auch einer Angststörung oder Depression dar [28,29,[31][32][33][34].…”
Section: Amnesie Und Pseudoerinnerungenunclassified
“…Delusional memories may originate from hallucinations and periods of delirium. These may all be influenced by sedation, analgesia and delirium management 4 . Few studies have described the nature and prevalence of frightening and traumatic memories early after ICU discharge.…”
mentioning
confidence: 99%